Activation of δ-opioid Receptors in Anterior Cingulate Cortex Alleviates Affective Pain in Rats. (1st July 2022) - Ma, Yang; Qin, Guo-Hua; Guo, Xia; Hao, Na; Shi, Yu; Li, Hui-Fen; Zhao, Xin; Li, Jian-Guo; Zhang, Ce; Zhang, Yu
Highlights: CFA induced conditioned place avoidance responses in rats. DADLE, the δ-opioid receptors agonist, administration in anterior cingulate cortex relieved conditioned place avoidance responses but not thermal pain sensitivity in CFA-injected rats. DADLE administration decreased firing frequency of anterior cingulate cortex pyramidal neurons in CFA-injected rats. DADLE perfusion inhibited the amplitude of anterior cingulate cortex pyramidal neurons NMDA current, not AMPA, in CFA-injected rats. DADLE administration decreased the phosphorylation of GluN1, GluN2A and GluN2B, subunits of NMDA receptors in anterior cingulate cortex in CFA-injected rats. Abstract: The negative emotions caused by persistent pain, called affective pain, are known to seriously affect human physical and mental health. The anterior cingulate cortex (ACC), especially the rostral ACC (rACC) plays a key role in the development of this affective pain. N-methyl-d -aspartate (NMDA) receptors, which are widely distributed in the ACC, are involved in the regulation of emotional behavior. It is well known that activation of opioid receptors can relieve pain, but whether it can alleviate affective pain is not clear. In the present study, conditioned place avoidance (CPA) responses induced by complete Freund's adjuvant (CFA) were used to represent the affective pain of place aversion. The behavioral measurements were synchronously combined with multichannel electrophysiological recordings of the discharge frequency of rACC pyramidal neurons to explore whether affective pain could be alleviated by the synthetic opioid [D-Ala2, D-Leu5]-Enkefalin (DADLE), an agonist of δ-opioid receptors. To further investigate this treatment as a mechanism for the relief of affective pain in CFA-treated animals, we used whole-cell patch recordings in slice preparations of the rACC region to determine the dose-dependent effects of DADLE on NMDA receptor-mediated currents. Then, western blot was used to determine levels of phosphorylated NMDA receptor subunits GluN1, GluN2 and GluN3 as affected by the δ-opioid receptor activation. The results showed that activation of δ-opioid receptors down-regulates the phosphorylation of NMDA receptor subunits, thereby inhibiting NMDA currents, decreasing the discharge frequency of rACC pyramidal neurons, and reversing the CPA response. Thus, δ-opioid receptor activation in the rACC region can alleviate affective pain.